Interventional study to find out effect of human chorionic gonadotropin and antioxidants on idiopathic male infertility - Padvi, Namrata V.; Singh, Pooja P.; Nadkarni, Kishore M.; Singh, Prabhakar M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Male contributes about 50% for cases with combined male and female infertility. When the cause is not known, it is term as idiopathic infertility. It affects 25% of men. Many advances have been made in reproductive medicine which provides great opportunities, couples which were considered untreatable now have got chance to have their own babies. Various ART procedures like ICSI have been proven as an efficient therapy in severe male factor infertility. However, the cost per cycle and complications such as multiple gestations cannot be ignored. Medical management of infertility can be specific or empirical depending on etiology. Specific medical management is use when certain etiology is identified. However, in absence of specific etiology use of empirical medical treatment can be attempted in order to improve treatment results. In this study our aim is to evaluate the effect of human chorionic gonadotropin (hCG) and antioxidants on semen parameters in men with idiopathic male infertility. Methods: Thirty men with abnormal semen parameters were included in study. Patients were treated with injection hCG-2000 IU three times a week for three months along with the antioxidants. After 3 months of treatment repeat semen analysis were performed and results were compared with pre-treated seminal parameters. Results: Results showed significant increase in sperm count (p value ≤ 0.001), total motility (p value=<0.001), and progressive forward motility (p value = <0.001), while no significant difference is seen in rest of the parameters. Conclusions: Use of hCG and antioxidants in idiopathic male infertility can significantly improve seminal parameters in idiopathic male infertility.